Enhancing the resilience of intercropping systems to changing moisture conditions in Africa through the integration of grain legumes: A meta-analysis - Adam, A.M.; Giller, K.E.; Rusinamhodzi, L.; Rasche, F.; Koomson, E.; Marohn, C.; Cadisch, G. (2025)
Problem Africa faces significant challenges due to climate change, which jeopardizes food security and the livelihoods of smallholder farmers who rely heavily on rain-fed agriculture. Although crop diversification has the potential to enhance resilience against climate variability, determining the optimal species compositions and agronomic practices for varying moisture conditions remains a significant challenge, despite extensive research efforts across the continent. Objectives This paper aims to evaluate the effectiveness of various intercropping systems and agronomic practices in response to changing moisture conditions, with the objective of enhancing smallholder resilience to climate change. Methods We conducted a comprehensive meta-analysis of existing studies (n = 1448) on intercropping systems in Africa, focusing on performance indicators such as the land equivalent ratio (LER), transgressive overyielding index (TOI), complementarity effect, and competition intensity. These indicators were evaluated in relation to moisture variability, quantified using the standardized precipitation evapotranspiration index (SPEI). Results The results reveal that moisture variability had a significant impact on intercropping performance and resource use. Intercropping consistently outperformed sole cropping, with an average TOI of 1.01 and LER of 1.45. Integrating grain legumes into intercropping systems enhanced performance and resource use by at least 11.5 % across all moisture conditions. The greatest benefits of legume integration were observed in root and tuber cropping systems (+78 % LER and +27 % TOI) compared to cereal-based systems (+39 % LER and +1 % TOI). This enhancement was attributed to reduced competition and stronger complementarity, particularly under drier conditions. Overall, our results indicate that legume-based intercropping systems are more resilient to moisture variability compared to non-legume systems, offering greater stability and productivity as moisture conditions fluctuate. Conclusions Our findings indicate that integrating grain legumes into intercropping systems is an effective strategy to enhance agricultural resilience in Africa. However, the effectiveness of such systems is dependent on specific moisture levels, highlighting the necessity of selecting optimal crop combinations and agronomic practices to maximize benefits. Implications This study offers valuable insights for policymakers, researchers, and farmers on the benefits of integrating grain legumes into root and tuber cropping systems as a low-hanging fruit climate-smart agricultural practice in Africa. Future research should focus on the long-term impacts and scalability of these practices.